2014
DOI: 10.1186/s12913-014-0637-7
|View full text |Cite
|
Sign up to set email alerts
|

Is Ghana’s pro-poor health insurance scheme really for the poor? Evidence from Northern Ghana

Abstract: BackgroundProtecting the poor and vulnerable against the cost of unforeseen ill health has become a global concern culminating in the 2005 World Health Assembly resolution urging member states to ensure financial protection to all citizens, especially children and women of reproductive age. Ghana provides financial protection to its citizens through the National Health Insurance Scheme (NHIS). Launched in 2004, its proponents claim that the NHIS is a pro-poor financial commitment that implements the World Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 19 publications
7
75
1
Order By: Relevance
“…In a study among women aged 15-49 years in the Upper East region of Ghana, it was observed that enrolment into the NHIS is influenced by household's socio-economic status and location of residence among others [48]. Perception of the quality of care at health facilities and perception of the NHIS are significant factors to enrolment.…”
Section: Discussionmentioning
confidence: 99%
“…In a study among women aged 15-49 years in the Upper East region of Ghana, it was observed that enrolment into the NHIS is influenced by household's socio-economic status and location of residence among others [48]. Perception of the quality of care at health facilities and perception of the NHIS are significant factors to enrolment.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study have implications for reducing inequity in access to healthcare, especially in light of the ongoing challenges to improve NHIS coverage [23,45] and efforts to achieve Universal Health Coverage. The results suggest that enabling factors (wealth) were a strong predictor for the use of both public and private health facilities.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Like Akazili et al 26 we found traditional African religious practitioners without insurance who saw illnesses as spiritually derived and saw little need for western medical practices. Other non-insured participants from a Christian sect saw God as healer and believed that illness was influenced or caused by sin.…”
Section: Religion Spirituality and National Healthcare Insurance Scmentioning
confidence: 93%